“Tag en Jorn med hjem”: Kunstbibliotekernes udlånssamlinger fra 1960’erne til 1990’erne - Line Ellegaard (Periskop – Forum for kunsthistorisk debat, 2025)
The 1964 Library Act allowed public libraries in Denmark to acquire ‘original art,’ including graphic works, for their lending collections. In the late 1960s and early 1970s, art departments were established in libraries in Gladsaxe, Lyngby, and Tranegården in Gentofte Municipality, followed by similar initiatives nationwide. These departments aimed to democratize access to art through lending collections, exhibitions, and events. By 1977, the collections comprised 989 works in Gladsaxe; 2,436 in Lyngby; and 1,150 in Gentofte. Yet, within two decades, most programs were dismantled, their collections sold or dispersed, and their legacy largely forgotten. This article examines the overlooked history of these art lending collections, analyzing their composition, acquisition criteria, and cultural significance. It argues that these art libraries were grounded in the welfare state’s cultural-political ideals of making art broadly accessible, while introducing a decentralized, radically different model of art dissemination. Unlike museums, which emphasize preservation and display, these collections, embedded within public libraries, prioritized circulation and everyday use. The history and legacy of public libraries’ art lending collections raises fundamental questions about art’s relationship to the common in the context of the welfare state, past and present.